Supercritical carbon dioxide for green polymer chemistry - Curia, Silvio (2016)
This thesis details novel research on the design of new approaches that might lead to a more sustainable polymer industry by combining the use of supercritical carbon dioxide, a commercially available immobilised enzyme and renewable monomers. First, the key themes explored in this thesis are outlined. Green polymer chemistry, biodegradable and renewable polymers, biocatalysts for polymerisations (i.e. enzymes) and supercritical carbon dioxide as a reaction medium for polymer synthesis and processing are introduced (Chapter 1). Then, the high-pressure equipment and characterisation techniques are detailed. The reaction vessel used extensively in this research work is meticulously described. The high-pressure fixed-volume view cell and the high-pressure rheometer are also detailed (Chapter 2). This chapter includes also the standard operating procedure (SOP) for each piece of equipment. In the first research chapter, the carbon dioxide-induced melting point depression of poly(e-caprolactone) is investigated; thorough rheometric studies are used to provide a rheological viewpoint to this phenomenon (Chapter 3). Shear-viscosity studies were performed in order to assess the advantages that high-pressure carbon dioxide could deliver for semi-crystalline polymer processing. Visual observations of the polymer plasticisation and comparisons with high-temperature studies are also shown. In the subsequent chapter, the development of a novel enzymatic low-temperature approach for the preparation of functional low molecular weight polyesters is detailed (Chapter 4). By exploiting the unique properties of supercritical carbon dioxide and an enzyme catalyst, polymerisations ordinarily conducted using metal catalysts in excess of 200 °C were successfully conducted at milder conditions. Functional molecules could be used to end-cap the chains, thus producing green telechelics. Then, this innovative synthetic approach was extended to the preparation of bio- based amphiphilic polymers, which could be useful for drugs encapsulation and as surfactants in detergent formulations (Chapter 5). Specifically, the self-assembly of these novel polymers and the stability of the aggregated structures in water were investigated in detail. Additionally, encapsulation of a highly lipophilic molecule (Coumarin-6) and surface tension studies provided a clear demonstration of the usefulness of these polymers for a wide range of applications. The final part of the thesis sums up the overall conclusions obtained from this research work and outlines possible opportunities for future research in this area (Chapter 6).